Systems analysis in AIS: potentials and pitfalls - Roo, Nina de; Hawkins, Richard; Schut, Marc; Salomons, Michael; Beshah, Tesfaye; Staal, Steven J.; Kassam, Shinan (Royal Tropical Institute, 2017)
Agricultural innovation systems are complex, multi-layered, and can be difficult to define and analyse. In this paper, we provide examples of ‘systems analysis’: describing the context, what was done, and how the outcomes informed broader research and development activities. The five cases describe analyses of: i) agricultural systems in North-West Vietnam; ii) household food security in Central Vietnam; iii) agricultural innovation systems in Central Africa; iv) wheat commodity systems in Sub-Saharan Africa, and v) the national agricultural research system in Papua New Guinea. These cases show that while there is no single best method to conduct systems analysis within a broader AIS approach, ‘good’ systems analysis demonstrates several common characteristics. Suggestions for system analysis in practice include: clarifying objectives and expectations; balancing breadth and depth; paying attention to power dynamics; avoiding an assumption of predictability; careful mixing of quantitative and qualitative methods; and a keeping a focus on informing action.